If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -3n = 8 Solving 2m + -3n = 8 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3n' to each side of the equation. 2m + -3n + 3n = 8 + 3n Combine like terms: -3n + 3n = 0 2m + 0 = 8 + 3n 2m = 8 + 3n Divide each side by '2'. m = 4 + 1.5n Simplifying m = 4 + 1.5n
| 10-4(6-x)+5x= | | 24-22=1 | | 8x-(4x-5)=17 | | 33/49*14/45*27/22 | | 3/2w-7/5w=-1/20 | | 4x-10=-6 | | (U+5)(u-3)= | | x-1/2x+14-x+5/9x+63 | | Ln(200)=ln(27x)+0.2x | | m+22=21 | | (2w^3-9w^5+2)10w^4= | | 2x+1=3y | | 8x^4(2-5x^2)= | | 180=12*x | | 6w^3(9w^7+4w)= | | 13=2*3.14*x | | (7/6n)+(1/2n)=5 | | 10.99=2*3.14*x | | 3x+6y=-2 | | 37.7=2*3.14*x | | 9x/2=49.5 | | x^2+x+5=65 | | 14x=49.5 | | (2w^2-7w^4+7)3w^5= | | 7x/2=49.5 | | 9w^2-9=0 | | 6y^2(10-9y^3)= | | 9(2x+5)=6(x-2)-3 | | 15*1.20= | | x^4+b*x^2+c=0 | | 2.40(1.20*15)= | | 5*x^3-x^2=0 |